Certification for Teachers and Lecturers and Its Implications For Staff Development - Madya, Suwarsih (Journal of English and Education (JEE), 2007)
The improvement of quality and relevancy,of education with the societal needs has been one of the big educational issues in Indonesia. It has been one of the considerations for the decision to adopt Education Act No. 20/2003 on National Education System. With its quality being improved, education will fulfill well its function, which is "to develop the capability, character, and civilization of the nation for enhancing its intellectual capability" (Education Act No.20/2003, Article 3).The enhancement of the intellectual life of the nation is in fact one of the four aims of our independence in 1945, as stated in the fourth paragraphs of the Preamble of the 1945 Constitution.The quality and relevancy of our national education will certainly contribute to the achievement of the god of our national education stated in Article 4 of the 2003 Education Act, which is "developing learners potentials so that they become persons-imbued with human values who are faithful and pious to one and only God; who possess morals and noble character; who are healthy, knowledgeable,-competent, creative; independent; and as citizens are democratic and responsible.".Since formal education is the main stream and it process-mostly takes place in classrooms in which teachers and lecturers play their various roles, the quality of teachers and lecturers is the one of the determining  factor in solving the problem of quality and relevancy. Related to this was the promulgation of "Teachers as Professionals" on 2 December 2005 by President Susilo Bambang Yudhoyono. in the same year. Law No."14/2005 on Teachers and Lecturers was declared valid.Certification is related to the needs for ensuring that teachers and lecturers as professionals possess the qualities which can contribute to the success in achieving quality education which is relevant for society needs which change with the developments resulting from the advancements of science and technology. This paper will explore aspects of certification and its implications for-teacher education, especially EFL teacher education, both pre-service and in-service.